2006
DOI: 10.1021/es061006c
|View full text |Cite
|
Sign up to set email alerts
|

PCBs, PCDD/Fs, and Organochlorine Pesticides in Farmed Atlantic Salmon from Maine, Eastern Canada, and Norway, and Wild Salmon from Alaska

Abstract: Farmed Atlantic salmon (Salmo salar) from Maine and eastern Canada, wild Alaskan Chinook salmon (Oncorhynchus tshawytscha), and organically farmed Norwegian salmon samples were analyzed for the presence of polychlorinated biphenyls (PCBs), dioxin-like PCBs, polychlorinated dibenzo-p-dioxins (PCDDs), dibenzo-p-furans (PCDFs), and chlorinated pesticides. PCDD and PCDF congeners were not detected in > 80% of the samples analyzed. Total PCB concentrations (7.2-29.5 ng/g, wet weight, ww) in the farmed salmon were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 29 publications
1
38
2
Order By: Relevance
“…The importance of identifying and labelling fish products in terms of risk and benefits, together with region of origin, has been suggested in order to allow consumer based choices and avoid unnecessary exposure to highly contaminated fish (Shaw et al, 2006 Although unlikely that all fish would be of ABT origin, ABT is estimated to contribute 67% of the total TEQ intake (Bocio et al, 2007 Dewailly, E., Blanchet, C., Gingras, S., Lemieux, S., Sauvé, L., Bergeron, J., Holub, B.J.,…”
Section: The International Society For the Study Of Fatty Acids And Lmentioning
confidence: 99%
“…The importance of identifying and labelling fish products in terms of risk and benefits, together with region of origin, has been suggested in order to allow consumer based choices and avoid unnecessary exposure to highly contaminated fish (Shaw et al, 2006 Although unlikely that all fish would be of ABT origin, ABT is estimated to contribute 67% of the total TEQ intake (Bocio et al, 2007 Dewailly, E., Blanchet, C., Gingras, S., Lemieux, S., Sauvé, L., Bergeron, J., Holub, B.J.,…”
Section: The International Society For the Study Of Fatty Acids And Lmentioning
confidence: 99%
“…Many of these chemicals occur at elevated levels in farmed and wild salmon (Isosaari et al 2006;Jacobs et al 2002;Shaw et al 2006). Studies on various salmonid species have identified several tissues as primary targets for TCDD-induced pathologic lesions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, farmed Atlantic salmon (Salmo salar) constitutes a significant portion of the world's salmon market [15]. Pesticides content in organs of these fish is strictly controlled; nevertheless, pollution of its habitat causes toxicants to accumulate in aquaculture objects [16].…”
Section: Resultsmentioning
confidence: 99%